2011
DOI: 10.1088/0957-4484/22/24/245105
|View full text |Cite
|
Sign up to set email alerts
|

Human haptoglobin phenotypes and concentration determination by nanogold-enhanced electrochemical impedance spectroscopy

Abstract: Haptoglobin (Hp) is an acute phase protein that binds free hemoglobin (Hb), preventing Hb-induced oxidative damage in the vascular system. There are three phenotypes in human Hp, whose heterogeneous polymorphic structures and varying concentrations in plasma have been attributed to the cause of diseases and outcome of clinical treatments. Different phenotypes of Hp may be composed of the same subunits but different copy numbers, rendering their determination difficult by a single procedure. In this study, we h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 36 publications
(59 reference statements)
0
8
0
Order By: Relevance
“…This concept is not entirely new. Cheng et al demonstrated that protein polymorphisms can be identified by the charge transfer resistance ratio of the protein-bound electrode from EIS measurement [29]. The authors proposed that a simple detection method based on measurement of relative charge transfer resistance ratio by EIS was a potential approach for investigating polymorphism due to changes in molecular weight [29].…”
Section: Resultsmentioning
confidence: 99%
“…This concept is not entirely new. Cheng et al demonstrated that protein polymorphisms can be identified by the charge transfer resistance ratio of the protein-bound electrode from EIS measurement [29]. The authors proposed that a simple detection method based on measurement of relative charge transfer resistance ratio by EIS was a potential approach for investigating polymorphism due to changes in molecular weight [29].…”
Section: Resultsmentioning
confidence: 99%
“…The value of R ct , which presents the charge transfer from the electrode during the Faradaic reaction, is the optimal parameter of the elements to analyse the Ag-Ab reaction of the working electrode in the Randles circuit. The nonhomogeneous surface of each probe would limit the application of EIS for routine clinical detection [21]. However, as indicated in the previous description, the relative charge transfer resistance ratio ( R ct(Analyte) /R ct(Ab w/BSA) ) can solve this problem and has been applied in previous studies [22].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study demonstrated that the haptoglobin (Hp) detection probe can distinguish phenotypes within 1-3 nm of each other and can quantify accurately down to picomolar levels of Hp 2-2, where the molecular size and weight are 13 nm and 190 kDa respectively [21]. EV71 is an icosahedral structure consisting of 60 copies of four capsid proteins.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations